“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism

Damaging and daunting: female journalists’ experiences of sexual harassment in the newsroom - North, Louise (Feminist Media Studies, 2016)
Female journalists’ experiences of sexual harassment are barely documented in the literature about Australian news journalism despite evidence of its ongoing prevalence. There have been some stories of harassment detailed in autobiographies by female journalists and the occasional article in the mainstream media about individual incidents, but it wasn’t until 1996 that a union survey provided statistical evidence of an industry-wide problem. That Media, Entertainment and Arts Alliance survey found that more than half of the 368 female participants had experienced sexual harassment at work. In 2012, I conducted the largest survey of female journalists in Australia finding that there was an increased number of respondents who had experienced sexual harassment in their workplaces. In a bid to better understand female journalists’ experiences of sexual harassment, this paper analyses written comments made by survey participants in relation to key questions about harassment. It finds that most downplay its seriousness and do not make formal reports because they fear victimisation or retaliation. As a consequence, a culture of secrecy hides a major industry problem where many women believe they should work it out themselves and that harassment is the price they have to pay for working in a male-dominated industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2015.1105275
Keywords: Myriam; Sexual harassment; female journalists; gender and work; gendered newsrooms; survey of Australian female journalists